Drug delivery systems - Ranade, Vasant V.; Cannon, John B. (Boca Raton, FL. : CRC Press)
"Drug delivery technologies represent a vast and vital area of research and development in pharmaceutics. The demand for innovative drug delivery systems continues to grow, and this growth drives a variety of new developments. Building on the foundation provided by the second edition, Drug Delivery Systems, Third Edition covers the latest in research, development, and regulations in industry and academia.The third edition of this popular book provides a comprehensive review of the latest research and development on drug delivery systems (including liposomal, transmucosal, transdermal, oral, polymeric, and monoclonal antibody directed delivery); it also contains a new chapter on nanoscience and technology for drug delivery along with cutting-edge business intelligence and strategies. These topics are spread into five sections: Site-specific drug delivery Polymers and implantable drug delivery systems Oral drug delivery Transdermal, transmucosal, ocular, and miscellaneous drug delivery systems Regulatory considerations and global outlook Written in a straightforward, clear, and concise manner, the authors provide a global perspective on current and future advances and market opportunities. The book answers the need for comprehensive information in a single resource for anyone venturing into this area of drug development and who desires an overview of the field, with extensive guidance on where to gain more information. Each chapter provides a table of marketed and investigational products, with numerous practical examples; the book also provides readers with a multitude of possible drug delivery systems that can be used to improve therapeutics, along with global and regulatory perspectives"--Provided by publisher